Strategies for Learning Arabic from Home at Islamic Boarding Schools During the Covid-19 Pandemic - Hafis, Luqman; Rix, Abraham; Arkaan, Booysen (Journal International of Lingua and Technology, 2022)
The current pandemic situation, which requires the learning process to be carried out from home online, makes it a challenge to learn Arabic. Initially, this policy was very much accepted by learners and educators with excitement. However, the reality is that this policy makes the learning process difficult to implement optimally. This research uses a qualitative descriptive method by collecting all data sources. Data source collection is carried out by interviewing teachers and students and documentation. Qualitative studies are carried out to analyze the problems faced by students and offer several possible recommendations to improve the quality of teaching Arabic as a foreign language based on student perceptions, taking into account the social context experienced during the learning process of the 2020-2021 academic year. The purpose of this research is to find problems that are being faced by students and educators in Islamic boarding schools during the pandemic and find the right solution to solve the problem so that the right strategy can be found for learning Arabic during this pandemic for a number of Islamic boarding schools.